Nonmonetary and nonreciprocal freecycling: Motivations for participating in online alternative giving communities. Issue 4 (13th February 2020) - Liu, Fan; Johnson, Zachary; Massiah, Carolyn; Lowrey, Tina M.
Abstract: This research examines consumers' participation in a nonmonetary, nonreciprocal form of online consumer exchange wherein consumers may decide to give only, receive only, or both give and receive. Given the lack of financial incentives or relational norms that would traditionally drive participation in this societally beneficial consumption activity for which we advance the term alternative giving, this research examines consumers' participation motivations. Are consumers, as prior research suggests, motivated to participate in alternative giving activities on the basis of prosocial motives or for other reasons? Through a content analysis of the online Freecycle Network, we found that participation is driven primarily by fundamental consumer needs and wants, though other prosocial, less materialistic factors are also drivers. Our findings also identify an inconsistency in product categories between what givers offer and what receivers seek, suggesting that supply–demand imbalances can emerge within alternative giving communities.